Growth response in broilers from dwarf dams as affected by climatic variation - DHINGRA, NEETA; BHARDWAJ, J K; KHAN, A G (The Indian Journal of Animal Sciences, 2013)
Performance of 2Â commercial broiler genotypes (G, G) was evaluated for growth responses up to 6 weeks of age in cold, moderate and hot climate (C) under 4 dietary regimes (T). Genotype G1 was produced from dwarfand G2 from normal broiler dams. Significantly (P< 0.05) superior body weights were obtained in G than G chicks at all ages in moderate and hot climates. Better feed conversion was found under hot followed by cold and moderate climates. Diet containing 25% crude protein and 3 000 kcal ME/kg feed supported superior growth irrespective of climate or genotype. Interaction of climate with genotype and diet was more important for G2 than G1 chicks. Genotype accounted for maximum variability for growth and feed efficiency. G2 was found to be more sensitive to climatic and nutritional variability than G1 genotype.